2014
DOI: 10.4321/s1886-36552014000400003
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the parental knowledge and attitude towards antibiotic usage and resistance among children in Tetovo, the Republic of Macedonia

Abstract: Objective:This study sought to explore the knowledge and attitudes of parents on the use of antibiotics among children that could serve as baseline data and provide further insight in planning and developing strategies for local health education purposes.Methods:A cross-sectional survey involving 500 parents who attended community pharmacies in Tetovo, Republic of Macedonia, was conducted using a self-administered questionnaire from October 2013 to January 2014. The questionnaire included demographics, knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
2
11

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 27 publications
(28 reference statements)
4
27
2
11
Order By: Relevance
“…Eleven studies identified that in private healthcare systems, regular follow‐ups with clinicians either by phone or home/office visit were more common. Parents reported more satisfaction when they knew and trusted their clinician and felt the clinician knew their family (Al‐Dossari, ; Alili‐Idrizi et al., ; Alkhaldi et al., ; Brookes‐Howell et al., ; Cabral et al., ; Chinnasami et al., ; Ecker et al., ; Panagakou et al., ; Rousounidis et al., ; Salazar et al., ; Zyoud et al., ). However, in three of the studies, parents felt that the clinician did not know their child or discuss their child's health with them, resulting in a feeling of lack of trust in the clinician and reduced compliance from parents (Alkhaldi et al., , Dwibedi et al., ; Wun et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eleven studies identified that in private healthcare systems, regular follow‐ups with clinicians either by phone or home/office visit were more common. Parents reported more satisfaction when they knew and trusted their clinician and felt the clinician knew their family (Al‐Dossari, ; Alili‐Idrizi et al., ; Alkhaldi et al., ; Brookes‐Howell et al., ; Cabral et al., ; Chinnasami et al., ; Ecker et al., ; Panagakou et al., ; Rousounidis et al., ; Salazar et al., ; Zyoud et al., ). However, in three of the studies, parents felt that the clinician did not know their child or discuss their child's health with them, resulting in a feeling of lack of trust in the clinician and reduced compliance from parents (Alkhaldi et al., , Dwibedi et al., ; Wun et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…A dominant theme, identified in the majority of the studies, was the variation in parental knowledge, attitudes and practices on antibiotic use and misuse in children with upper respiratory tract infections (URTIs) (Agarwal et al., ; Al‐Dossari, ; Alili‐Idrizi et al., ; Alkhaldi et al., ; Brookes‐Howell et al., ; Chan & Tang, ; Chinnasami et al., ; Ecker et al., ; Farha, Suyagh, Alsakran, Alsous, & Alefishat, ; Finkelstein et al., ; Panagakou et al., ; Rousounidis et al., ; Salazar et al., ; Wun et al., ; Yu et al., ; Zyoud et al., ). In fifteen studies, the levels of education were cited as significant to parents' knowledge (Agarwal et al., ; Al‐Dossari, ; Alili‐Idrizi et al., ; Alkhaldi et al., ; Chan & Tang, ; Chinnasami et al., ; Dwibedi et al., ; Ecker et al., ; Farha et al., ; Panagakou et al., ; Rousounidis et al., ; Salazar et al., ; Salonga, ; Vaz et al., ; Yu et al., ). In four studies (Agarwal et al., ; Al‐Dossari, ; Ecker et al., ; Zyoud et al., ), parents could not generally identify or name an antibiotic and only two studies cited that parents had knowledge of the importance of completing antibiotic courses (Agarwal et al., ; Ecker et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ancak bizim sonuçlarımızdan farklı olarak bu çalışmalarda katılımcıların antibiyotik kullanımıyla ilgili bilgi düzeyleri annelerin yaş, eğitim durumu, sosyoekonomik durum ve yaşadığı bölgeyle ilişkili bulunmuştur. [13][14][15][16] Parimi ve ark. 'nın çalışmasında özel sağlık güvencesine sahip olmak, bilgi düzeyinin yüksek olması ile ilişkili bulunmuştur.…”
Section: Discussionunclassified